The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1039/c2dt30221g
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis and tunable luminescence properties of Y2(WO4)3:Ln3+ (Ln = Eu, Yb/Er, Yb/Tm and Yb/Ho) 3D hierarchical architectures

Abstract: Yttrium tungstate precursors with novel 3D hierarchical architectures assembled from nanosheet building blocks were successfully synthesized by a hydrothermal method with the assistance of sodium dodecyl benzenesulfonate (SDBS). After calcination, the precursors were easily converted to Y(2)(WO(4))(3) without an obvious change in morphology. The as-prepared precursors and Y(2)(WO(4))(3) were characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 70 publications
(67 reference statements)
1
43
0
Order By: Relevance
“…Therefore, they are recently considered as promising host materials for rare-earth luminescent centers because of the special properties of WO 4 2-& Guixia Liu liuguixia22@163.com group [11][12][13][14]. From the report of Huang et al [15], it was seen that tungstate host essentially showed a little weaker blue emission at room temperature compared to the absorption in excitation spectrum, owing to efficient energy transfer from WO 4 2-group to activators. Liu et al [16] had also discovered that NaY(WO 4 ) 2 exhibited a broad emission centered at approximately 469 nm without doping Ln 3? ions, and the intensity of this emission decreased when Ln 3?…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, they are recently considered as promising host materials for rare-earth luminescent centers because of the special properties of WO 4 2-& Guixia Liu liuguixia22@163.com group [11][12][13][14]. From the report of Huang et al [15], it was seen that tungstate host essentially showed a little weaker blue emission at room temperature compared to the absorption in excitation spectrum, owing to efficient energy transfer from WO 4 2-group to activators. Liu et al [16] had also discovered that NaY(WO 4 ) 2 exhibited a broad emission centered at approximately 469 nm without doping Ln 3? ions, and the intensity of this emission decreased when Ln 3?…”
Section: Introductionmentioning
confidence: 96%
“…The crystallite size values for Ca 0.5 Y(WO 4 ) 2 doped with Pr 3+ , Sm 3+ , Eu 3+ , Tb 3+ , Dy 3+ and Yb 3+ /Er 3+ are found between 30.0 and 42.0 nm and the cell parameters and its volume are given in Table S1 (Supplementary Material). 7 Scanning electron microscopy and energy dispersive X-ray analysis were used to determine the morphology and chemical composition of elements in the prepared sample. In this context, as a representative candidate for the analysis, 0.…”
Section: Structural and Morphological Studiesmentioning
confidence: 99%
“…In modern materials science, the ability to prepare nano-and microstructures with well-defined morphology and excellent monodispersity in bulk scale is an essential requirement for applications of materials [1,2]. Till now, it is generally accepted that the morphology, dimensionality, and crystal structure of the materials all play important roles in the electronic, optical, magnetic, catalytic, chemical, and other physical properties [3][4][5].…”
Section: Introductionmentioning
confidence: 99%